In-Vitro Study Of Antifungal Activity Of Various Commercially Available Itra (Volatile Plant Oil) Against The Keratinophilic Fungi Isolated From Soil - PRABAL SINGH; RUCHI BUNDIWALE; LK DWIVEDI (International Journal of Pharma and Bio Sciences, 2011)
Keratophilic fungi, a type of dermatophytes cause infection to hair, glabrous skin and nails of human beings and animals. Soil is well known to be supporting the transient existence of them. The volatile plant oils have been of concern recently to develop a new antifungal agent. The present study attempts to evaluate four different commercially available Itra- Bella (Lonicera x bella zabel), Kewda (Pandanus odoratissimus), Rajnigandha (Polianthes tuberosa) and Mogra (Jasminum sambac) for their antifungal activity against the Aspergillus flavus, Trichophyton mentagrophytes, Trichophyton tonsurans, Trichophyton verrucosum, Epidermatophyton floccosum and Microsporum nanum isolated from soil. A few among the selected Itra were observed and were found to be showing better antifungal activity than existing antifungal drugs like Terbinafine, Itraconazole and Fluconazole (taken as control). The maximum effect was shown by Bella against T.tosurans with inhibitory zone of 47mm. The paper concludes that the Itra can be used as antifungal agent against prevalent keratinophilic fungi.